Prognostic Impact of Urokinase Plasminogen Activator Receptor Expression in Pancreatic Cancer: Malignant Versus Stromal Cells - Susanna WL de Geus; Victor M Baart; Martin C Boonstra; Peter JK Kuppen; Hendrica AJM Prevoo; Andrew P Mazar; Bert A Bonsing; Hans Morreau; Cornelis JH van de Velde; Alexander L Vahrmeijer; Cornelis FM Sier (Biomarker Insights, 2017)
The urokinase plasminogen activator receptor (uPAR) has been proposed as a potential prognostic factor for various malignancies. The aim of this study is to assess the prognostic value of uPAR expression in neoplastic and stromal cells of patients with pancreatic adenocarcinoma. Urokinase plasminogen activator receptor expression was determined by immunohistochemistry in 122 pancreatic ductal adenocarcinomas. Kaplan-Meier and Cox regression analyses were used to determine the association with survival. Respectively 66%, 82% and 62% of patients with pancreatic cancer expressed uPAR in neoplastic cells, stromal, and in both combined. Multivariate analysis showed a significant inverse association between uPAR expression in both neoplastic and stromal cells and overall survival. The prognostic impact of uPAR in stromal cells is substantial, but not as pronounced as that of uPAR expression in neoplastic cells. This study suggests a role for uPAR as a biomarker to single out higher risk subgroups of patients with pancreatic cancer.